Yeast aquaporin regulation by 4‐hydroxynonenal is implicated in oxidative stress response. Issue 5 (24th March 2017) - Rodrigues, Claudia; Tartaro Bujak, Ivana; Mihaljević, Branka; Soveral, Graça; Cipak Gasparovic, Ana
Summary: Reactive oxygen species, especially hydrogen peroxide (H2 O2 ), contribute to functional molecular impairment and cellular damage, but also are necessary in normal cellular metabolism, and in low doses play stimulatory role in cell proliferation and stress resistance. In parallel, reactive aldehydes such as 4‐hydroxynonenal (HNE), are lipid peroxidation breakdown products which also contribute to regulation of numerous cellular processes. Recently, channeling of H2 O2 by some mammalian aquaporin isoforms has been reported and suggested to contribute to aquaporin involvement in cancer malignancies, although the mechanism by which these membrane water channels are implicated in oxidative stress is not clear. In this study, two yeast models with increased levels of membrane polyunsaturated fatty acids (PUFAs) and aquaporin AQY1 overexpression, respectively, were used to evaluate their interplay in cell's oxidative status. In particular, the aim of the study was to investigate if HNE accumulation could affect aquaporin function with an outcome in oxidative stress response. The data showed that induction of aquaporin expression by PUFAs results in increased water permeability in yeast membranes and that AQY1 activity is impaired by HNE. Moreover, AQY1 expression increases cellular sensitivity to oxidative stress by facilitating H2 O2 influx. On the other hand, AQY1 expression has no influence on the cellular antioxidant GSH levels and catalase activity. These results strongly suggest that aquaporins are important players in oxidative stress response and could contribute to regulation of cellular processes by regulation of H2 O2 influx. © 2017 IUBMB Life, 69(5):355–362, 2017